A Test of the Errors‐in‐Expectations Explanation of the Value/Glamour Stock Returns Performance: Evidence from Analysts' Forecasts - Doukas, John A.; Kim, Chansog (Francis); Pantzalis, Christos (Journal of Finance, 2002)
ABSTRACT Several empirical studies show that investment strategies that favor the purchase of stocks with low prices relative to conventional measures of value yield higher returns. Some of these studies imply that investors are too optimistic about (glamour) stocks that have had good performance in the recent past and too pessimistic about (value) stocks that have performed poorly. We examine whether investors systematically overestimate (underestimate) the future earnings performance of glamour (value) stocks over the 1976 to 1997 period. Our results fail to support the extrapolation hypothesis that posits that the superior performance of value stocks is because investors make systematic errors in predicting future growth in earnings of out‐of‐favor stocks.